PENGARUH KOMPETENSI, KEBIJAKAN INTERNAL DAN KOMITMEN KEPALA SKPK TERHADAP EFEKTIVITAS PENGGUNAAN E-PURCHASING PADA PEMERINTAHAN KABUPATEN BIREUEN - Suryani Suryani; Zainuddin Iba (IndOmera, 2026)
This study aims to examine the influence of competency, internal policies, and commitment of the Head of the Regional Government Work Unit (SKPK) on the effectiveness of e-purchasing. The study was conducted on SKPK Heads of the Bireuen Regency Government, using a quantitative associative method using path analysis. The results found: (1) competency significantly influences the effectiveness of e-purchasing, with a value of 55.55%. Internal policies have a 46.28% influence. And commitment has a 46.39% influence. (2) Competence, internal policies, and commitment simultaneously contribute positively to the effectiveness of e-purchasing in the Bireuen Regency Government, with a value of 87,6%. (3) There is a causal relationship between the variables of competency, internal policies, and commitment, with an average value of 5.5%.